The geochemical characteristics of Tazhong crude oils from the Tarim Basin, northwestern China - Yungan Liang; Jianbing Xu; Wenwen Li; Bin Cheng; Qian Deng; Haizu Zhang; Zewen Liao (Energy Exploration & Exploitation, 2018)
Recent exploration work in the Tazhong district has gradually transferred to the exploitation of high and over mature oils in deep and ultra-deep layers. This has proved problematic, however, as the distribution of crude oils in the Tazhong is complex. This means that the geochemical characterization of high and over mature oils, especially for light crude oils, have become increasingly important. The stability of concerted ring structure of aromatics makes them having stronger thermal stability and resistance to biodegradation. This means that there are abundant aromatic compounds in high and over mature oils. This study presents a series of geochemical analyses of the maturity parameters of 89 crude oils from the Tazhong area, including stable carbon and hydrogen isotope analyses of compounds from 43 light crude oils. These analyses are then compared with other data from the Tazhong Number I fault zone, as well as the Tazhong Number 10 and Tazhong Uplift structural zones. Results show that the geochemical parameters of oils from Tazhong Number I fault zone generally encompass a wider range than those from the Tazhong Number 10 structural zone, which indicates that the Tazhong Number I slope belt is more active than its counterpart structural belt and generates oils with more complex geochemical characteristics. The positive correlation between the toluene/methyl cyclohexane ratio and the dibenzothiophene/phenanthrene ratio, as well as with the naphthalene/phenanthrene ratio indicates that aromatization parameters can be used to evaluate the maturity of light crude oils, and there may be inherited relationships between toluene and methyl cyclohexane in crude oils.